2018
DOI: 10.1051/e3sconf/20182801042
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water-soluble elements in PM2.5, PM10, and PM2.5-10 collected in the surroundings of power plants

Abstract: Abstract. The analysis reported in this study was performed to characterize the concentrations and water-soluble content of trace elements (As, Cd, Co, Cr, Hg, Mn, Ni, Pb, Sb and Se) in PM2.5, PM10 and PM2.5-10 samples collected in the surroundings of power plants in southern Poland. The solubility of trace elements bound to PM2.5 and PM10 was higher than for PM2.5-10, and in most cases, significant differences were revealed in the relative percentage concentrations of the water-soluble fractions. The occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Investigations conducted by Wiseman and Zereini ( 2014 ) revealed the high solubility of As and Sb in an artificially prepared body fluid that naturally occurs in human lungs. The author’s research (Zajusz-Zubek 2016 ) also revealed the highest percentage contents of these elements in the most mobile fraction F1. This may indicate a high health risk due to the content of the listed elements at the selected measurement points.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Investigations conducted by Wiseman and Zereini ( 2014 ) revealed the high solubility of As and Sb in an artificially prepared body fluid that naturally occurs in human lungs. The author’s research (Zajusz-Zubek 2016 ) also revealed the highest percentage contents of these elements in the most mobile fraction F1. This may indicate a high health risk due to the content of the listed elements at the selected measurement points.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, in the vicinity of coking plants, a relatively high content of Pb in the carbonate and oxide fraction (F2) in PM2.5 and PM10 was found, reaching 46.36 and 50.49%, respectively. The results of these investigations have been presented in the author’s publication (Zajusz-Zubek 2016 ). The presence of Pb, mainly in the F2 fraction in total suspended particulates (TSP), was also signaled in the investigations conducted in urban areas in China (Schleicher et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations